Production and characterization of keratin microparticles obtained from wool fibers by cryogenic milling method - Duman, Seyma; Kucuk, Merve (Taylor & Francis Inc, 2022)
In this study, keratin particles were obtained from wool fibers by the cryogenic milling method without utilizing any chemical solvent. The optimal milling period and low energy expenditures are the predominant advantages of the proposed method as the first attempt to incorporate cryogenic milling into the process of keratin production from a wool resource. The configuration, size distribution, surface area, crystallinity, chemical composition, and thermal properties of keratin particles were assessed by a particle size analyzer, stereo microscope, Brunauer-Emmett-Teller (TM) surface analyzer, scanning electron microscope, x-ray diffractometer, Fourier transform infrared spectroscopy, differential scanning calorimetry, and thermogravimetric analyzer measurements. The characterization results indicate no alteration in the structural and chemical properties of keratin microparticles after cryogenic milling. The procurement of waste fibers from wool, one of the main raw materials of the textile industry, and processing them into keratin particles by an environment-friendly and innovative method can be considered the pioneering aspects of this study.
Keywords: Solid textile waste; wool fibers; cryogenic milling; keratin microparticles; particle characterization